2007
DOI: 10.4141/p06-059
|View full text |Cite
|
Sign up to set email alerts
|

Inter simple sequence repeat (ISSR) to assess genetic diversity within a collection of wild lingonberry (Vaccinium vitis-idaea L.) clones

Abstract: Debnath, S. C. 2007. Inter simple sequence repeat (ISSR) to assess genetic diversity within a collection of wild lingonberry (Vaccinium vitis-idaea L.) clones. Can. J. Plant Sci. 87: 337-344. Forty-three wild lingonberry [Vaccinium vitis-idaea ssp. minus (Lodd) Hult.] clones collected from four Canadian provinces were assessed for genetic variability by using inter simple sequence repeat (ISSR). Fifteen primers generated 356 polymorphic ISSR-PCR bands. A substantial degree of genetic diversity was found among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 13 publications
10
40
0
Order By: Relevance
“…The knowledge on optimal amplification condition and polymorphism level becomes useful data for cranberry researchers. While ISSRs were also found effective in diversity analysis of lowbush blueberry (Debnath 2009) and lingonberry (Debnath 2007b), EST-SSR and EST-PCR markers were used in blueberry (Boches et al 2006) and cranberry (Bell et al 2008), respectively. Zalapa et al (2014 and Bassil et al (2009) reported the use of SSR and EST-SSR markers, respectively, in discriminating cranberries.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge on optimal amplification condition and polymorphism level becomes useful data for cranberry researchers. While ISSRs were also found effective in diversity analysis of lowbush blueberry (Debnath 2009) and lingonberry (Debnath 2007b), EST-SSR and EST-PCR markers were used in blueberry (Boches et al 2006) and cranberry (Bell et al 2008), respectively. Zalapa et al (2014 and Bassil et al (2009) reported the use of SSR and EST-SSR markers, respectively, in discriminating cranberries.…”
Section: Discussionmentioning
confidence: 99%
“…The number of polymorphic bands (12.7 per primer in the two tissues) obtained with ISSR markers in V. corymbosum cultivars was slightly lower compared to other studies in other Vaccinium species [Debnath (2007) in V. vitis-idaea (23.7 polymorphic bands), Debnath (2009) in V. angustifolium (17 polymorphic bands) and Yakimowski and Eckert (2008) in V. stamineum (18 polymorphic bands)]. The differences in the number of polymorphic bands in these studies can be explained because different species were studied, although they all belong to the Vaccinium genus.…”
Section: Resultsmentioning
confidence: 67%
“…The high genetic diversity between V. corymbosum cultivars could be hypothetically explained by the high ploidy level (Boches et al 2006) and the origin of each cultivar that consequently makes the blueberry a highly heterozygote genetic structure. High levels of genetic variation were also observed with these molecular markers in V. myrtillus (Albert et al 2005), Vaccinium vitis-idaea (Debnath 2007) and V. angustifolium (Debnath 2009). …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations